2018
DOI: 10.2147/jpr.s166617
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and spinal cord stimulation for the treatment of failed back surgery syndrome refractory pain

Abstract: ObjectiveThis study aimed to evaluate pain and its symptoms in patients with failed back surgery syndrome (FBSS) refractory to other therapies, treated with a combination of delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD), in association with spinal cord stimulation (SCS).SettingsOutpatients referred at Pain Unit of San Vincenzo Hospital in Taormina (Italy), between September 2014 and January 2016.SubjectsEleven FBSS patients diagnosed with neuropathic pain using the Douleur Neuropathique 4 questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
0
22
0
1
Order By: Relevance
“…Combination of the two often improved upon the deleterious and psychoactive effects of THC-only administration (Ueberall et al, 2019). The CBD : THC formulations were effective at reducing mean pain scores in chronic pain patients with multiple sclerosis, improved neurophysical measurements in response to noxious stimuli, reduced intractable chronic pain in advanced cancer, and improved refractory/neuropathic pain following failed spinal cord surgery (Rog et al, 2005;Conte et al, 2009;Johnson et al, 2010;Portenoy et al, 2012;Mondello et al, 2018). There is contradictory evidence that CBD : THC treatment does not always relieve chronic pain in patients with brachial plexus avulsion or advanced-cancer, as evidenced by studies in two-independent cohorts, thus indicating the heterogeneity in disease contexts for which cannabinoids may be effective; of note, although pain was not significantly improved, patients in these studies indicated an improved quality of life (Berman et al, 2004;Fallon et al, 2017;Lichtman et al, 2018).…”
Section: Clinical Outcomes For Cannabidiol In Intractable Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of the two often improved upon the deleterious and psychoactive effects of THC-only administration (Ueberall et al, 2019). The CBD : THC formulations were effective at reducing mean pain scores in chronic pain patients with multiple sclerosis, improved neurophysical measurements in response to noxious stimuli, reduced intractable chronic pain in advanced cancer, and improved refractory/neuropathic pain following failed spinal cord surgery (Rog et al, 2005;Conte et al, 2009;Johnson et al, 2010;Portenoy et al, 2012;Mondello et al, 2018). There is contradictory evidence that CBD : THC treatment does not always relieve chronic pain in patients with brachial plexus avulsion or advanced-cancer, as evidenced by studies in two-independent cohorts, thus indicating the heterogeneity in disease contexts for which cannabinoids may be effective; of note, although pain was not significantly improved, patients in these studies indicated an improved quality of life (Berman et al, 2004;Fallon et al, 2017;Lichtman et al, 2018).…”
Section: Clinical Outcomes For Cannabidiol In Intractable Chronic Painmentioning
confidence: 99%
“…Humans improved refractory/neuropathic pain; Patient-reported ↓ chronic pain; ↑ quality of life; Improved responses to noxious stimuli Johnson et al, 2013;Sellers et al, 2013;Ueberall et al, 2019;(Rog et al, 2005;Conte et al, 2009;Johnson et al, 2010;Portenoy et al, 2012;Mondello et al, 2018) (Berman et al, 2004Fallon et al, 2017;Lichtman et al, 2018) CBD, cannabidiol; THC, tetrahydrocannabinol; HEK cells, human embryonic kidney cells; HES cells, human endometrial stroma cells; JAr cells, human choriocarcinoma cells; BeWo cells, human placental cell line from choriocarcinoma; MCF7/P-gp cells, MCF-7 breast carcinoma cells expressing P-glycoprotein; NIH, National Institutes of Health National Institute on Drug Abuse; NS, not specified. The superscripted numbers corresponds with the vendor in the source and the cited article within that row.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Although our results were not statistically significant, pharmacological modulation of the cannabinoid system using a combination of delta‐9‐tetrahydrocannabinol/cannabidiol proved useful in FBSS patients who are refractory to other available therapeutic strategies, including SCS. (2)…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is an increased demand for alternative therapies. (2) Chronic pain is believed to involve an interaction between biological and psychological factors. Psychological factors are used to explain both the persistence and exacerbations of the disease, whereas biological factors account for damage to the patient and include genetic markers, on which research to date has been scarce.…”
Section: Introductionmentioning
confidence: 99%
“…48 CBD is a non-psychoactive cannabinoid, and associated with anticonvulsant, anxiolytic and sedative effects. 49,50 There is also a growing body of evidence for the use of THC and CBD, both individually and in combination sprays (Nabiximol), for the management of chronic pain, in the setting of multiple sclerosis, 51,52 spinal cord injury-related neuropathic pain, 53 and refractory advanced cancer-related pain. [54][55][56] Two classes of cannabinoid receptors have been identified, CB 1 and CB 2 receptors, which are part of the endocannabinoid system.…”
Section: Introductionmentioning
confidence: 99%